SOCIAL DIMENSION OF THE EU FULFILLING DEMOCRATIC LEGITIMACY OF INTEGRATION GROUP - Dudová, Iveta; Stanek, Vojtech (European Scientific Journal, ESJ, 2015)
The social aspect of market economy is a pillar resulting from historical experience and geographic context. The EU is a model of social dimension of integration. The current welfare state encounters fundamental problems related to social changes like long-term unemployment, demographic ageing, intergenerational tension and emergence of new risks. The existing inability of the EU to eliminate the crisis results in unexpected political events and increases the risk in development sustainability. Solution is in accelerated economic growth and welfare state policy reform from the perspective of the focus on social investment and knowledge economy.